PENINGKATAN OPTIMASI DISTRIBUSI KURMA MELALUI EFISIENSI BIAYA DENGAN PENDEKATAN METODE TRANSPORTASI: STUDI KASUS DI PT. XYZ - Resa Al Khauzar Victorio; Nuriah Yuliati; Ika Sari Tondang (International Journal of Multidisciplinary Research and Literature, 2023)
PT. XYZ faces several challenges in optimizing the distribution of dates, especially in terms of costs and delivery allocation. In the efficiency of the cost of distribution of dates, companies need to reduce operational costs associated with distribution activities. The research objective to be achieved is to analyze the minimum cost of distributing dates at PT. XYZ with the approach of transportation methods. The transportation methods used in this study are Vogel's Approximation Method, Least Cost, North-West Corner, and Stepping Stones. Vogel's Approximation Method, Least Cost, and North-West Corner are used to find the initial solution. While the Stepping Stones method is used to find the final solution. Data processing is carried out using Cbom-Atozmath and POM-QM to obtain fast, detailed, and accurate results. Data processing using the VAM (Vogel's Approximation Method) method results in a total date distribution cost of IDR 171,983,5100.00. Data processing using the NWC (North-West Corner) method resulted in a total date distribution cost of IDR 171,983,5100.00. Data processing using the LC (Least Cost) method resulted in a total date distribution cost of IDR 1,719,835,100.00. The results of calculations using the Cbom-Atozmath and POM-QM software also show the same results. The use of transportation methods to streamline the cost of distributing dates to the Company resulted in savings of Rp. 69,224,000.00. The total cost of distribution of dates by PT. XYZ before efficiency using the transportation method was Rp. 1,789,059,100. The total cost of distribution of dates by PT. XYZ after efficiency using the transportation method was Rp. 1,719,835,100.00